Strategic Human Resource Management in Hotel Industries - Mohanty, Sasmita; Pradhan , Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Three methods have governed the area of "Strategic Human Resource Management" (SHRM), namely the Standard or Good Practice, Contingency or the best-fit and "Resource Based View" (RBV). This study demonstrates evidence for case study enterprises in worldwide hotel industry to simultaneously or collaboratively adopt such approaches. Results suggest that there has been significant evidence of the cumulative use of the first two methods but that all companies had difficulty achieving the SHRM RBV strategy. Ultimately it was observed that achieving distinction across SHRM activities was difficult due to specific market influences. The aim of this study is to examine proof of the mixed version of the SHRM methods by case studies of foreign hotel companies. This sector introduces a particularly appropriate sector background, where there is a brief and continuous history of rapid development, and the propaganda suggests that' a hotel is only as great as its manager.' Subsidiary or unit managers have typically been seen as' strategic human resources' responsible for the creation of profitable units via their generic-business management skills, hospitality-specific, leadership and expertise.